Trends in reasons for permanent teeth extractions in Sebha city/Libya from 1998 to 2025: Comparison between two clinical samples - Jaeidah, Sherifa; Wenisa Arrish (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted to determine the reasons for dental extraction of permanent teeth in Sebha in 2025 and to describe changes in reasons for dental extraction in Sebha city/Libya, over 27 years, based on two clinical surveys collected in 1998 and 2025. This cross-sectional study was conducted at Sebha University’s dental general practice, and dentists recruited over a 7-month period documented clinical data for 525 patients, aged 15 to 60, who had dental extractions. Age, sex, education, attendance pattern, request type, reason for extraction, and tooth type were among the clinical variables that were included. The data collected were analyzed and compared with the data of the 1998 survey. Caries remains the primary cause of extractions (83.1%), followed by periodontal disease (9.4%). After comparison between two surveys in 1998 and 2025, there were trend changes related to the age, sex, education, where dental extractions became more common in the 30-60 age group (67.4%) and in women than men (38.6% for males and 61.3% for females), and in those with a university degree (48.4%). Caries remains the most common reason for dental extractions in Sebha city, Libya, based on a comparison of data from two surveys that were carried out more than 27 years apart. The percentage of dental extractions, however, is increasing for both age groups, becoming more common as people age, and is more common among women and those with a university education. This study highlights the significance of caries and periodontal disease prevention programs for adult.